Telemedicine in the OECD: An umbrella review of clinical and cost-effectiveness, patient experience and implementation. - Nkiruka D Eze; Céu Mateus; Tiago Cravo Oliveira Hashiguchi (PLoS ONE, 2020)
INTRODUCTION:Patients and policy makers alike have high expectations for the use of digital technologies as tools to improve health care service quality at a sustainable cost. Many countries within the Organisation for Economic Co-operation and Development (OECD) are investing in telemedicine initiatives, and a large and growing body of peer-reviewed studies on the topic has developed, as a consequence. Nonetheless, telemedicine is still not used at scale within the OECD. Seeking to provide a snapshot of the evidence on the use of telemedicine in the OECD, this umbrella review of systematic reviews summarizes findings on four areas of policy relevance: clinical and cost-effectiveness, patient experience, and implementation. METHODS:This review followed a prior written, unregistered protocol. Four databases (PubMed/Medline, CRD, and Cochrane Library) were searched for systematic reviews or meta-analyses published between January 2014 and February 2019. Based on the inclusion criteria, 98 systematic reviews were selected for analysis. Due to substantial heterogeneity, a meta-analysis was not conducted. The quality of included reviews was assessed using the AMSTAR 2 tool. RESULTS:Most reviews (n = 53) focused on effectiveness, followed by cost-effectiveness (n = 18), implementation (n = 17) and patient experience (n = 15). Eighty-three percent of clinical effectiveness reviews found telemedicine at least as effective as face-to-face care, and thirty-nine percent of cost-effectivenss reviews found telemedicine to be cost saving or cost-effective. Patients reported high acceptance of telemedicine and the most common barriers to implementation were usability and lack of reimbursement. However, the methodological quality of most reviews was low to critically low which limits generalizability and applicability of findings. CONCLUSION:This umbrella review finds that telemedicine interventions can improve glycemic control in diabetic patients; reduce mortality and hospitalization due to chronic heart failure; help patients manage pain and increase their physical activity; improve mental health, diet quality and nutrition; and reduce exacerbations associated with respiratory diseases like asthma. In certain disease and specialty areas, telemedicine may be a less effective way to deliver care. While there is evidence that telemedicine can be cost-effective, generalizability is hindered by poor quality and reporting standards. This umbrella review also finds that patients report high levels of acceptance and satisfaction with telemedicine interventions, but that important barriers to wider use remain.